Buckling of axially loaded sandwich composite panels with reinforced calcium silicate faces and polyurethane cores. (September 2015) - Tang, Zhirong; Zha, Xiaoxiong; Ma, Jinquan
This paper investigates the buckling properties of a new building sandwich composite panel composed of two fiber-reinforced calcium silicate faces and a formed polyurethane core material. In order to predict the global buckling load of sandwich panels subjected to axial loads, the buckling formulae are theoretically derived and suggested in design. Using the method of effective length factor, both buckling formulae for fixed–fixed sandwich panel and hinged–hinged one are unified into the same form. The buckling formulae are verified by axial load tests, finite element (FE) software ABAQUS. Comparing the theoretical formula derived with FE modeling results, a good agreement is obtained and this illustrates the accuracy of the unified formula. To analyze the influence of both geometrical and material parameters on the buckling load, a sensitivity analysis is conducted. The results show that boundary condition, length, and total thickness have large influence on buckling load. The core shear modulus has large influence on buckling load of short sandwich panels and this influence becomes less important with the increasing length. The accuracy degree of theoretical result in hinged condition is mainly affected by length and initial geometric imperfection. The variation of core shear modulus has little effect on error.